Improving the Quality of Madrasah Ibtidaiyah Through Transformational Leadership - Ahmad, Farid Farid (LJPI UI Bunga Bangsa Cirebon, 2024)
Purpose: This research aims to explore more deeply the application of transformational leadership in Islamic education and its role in improving educational standards and school performance, as well as realizing the importance of leadership in utilizing the potential of school resources. Methods: This research uses descriptive research methods with a qualitative approach. This is because researchers carry out direct observations in the field to observe and provide an accurate picture of the reality that occurs in the field. Results: The research results show that madrasa heads bear the responsibility of supervising all aspects of educational activities, starting from managing teachers and students, developing curriculum and programs to building relationships with parents and the community. By using a three-stage strategy that includes input, process, and output, this research shows that there is a strict selection process for students and teachers who enter the input stage, while remaining focused on optimizing the learning process to produce quality educational results. These strategies are intricately designed to complement and strengthen each other, fostering an inclusive and conducive educational environment. Conclusion: These findings underscore the positive impact of transformational leadership on the overall educational landscape at MI Wali Songo Asy-Syirbaany, South Tangerang City, where madrasa heads, through inclusive and astute leadership, prioritize improving the quality of education. Therefore, this research explains the important role of transformational leadership in raising educational standards and improving school performance, and offers valuable insights for improving the quality of education in similar settings.